Interplay among cell migration, shaping, and traction force on a matrix with cell-scale stiffness heterogeneity - Hiroyuki Ebata; Satoru Kidoaki (Biophysics and Physicobiology, 2022)
In living tissues where cells migrate, the spatial distribution of mechanical properties, especially matrix stiffness, is generally heterogeneous, with cell scales ranging from 10 to 1000 μm. Since cell migration in the body plays a critical role in morphogenesis, wound healing, and cancer metastasis, it is essential to understand the migratory dynamics on the matrix with cell-scale stiffness heterogeneity. In general, cell migration is driven by the extension and contraction of the cell body owing to the force from actin polymerization and myosin motors in the actomyosin cytoskeleton. When a cell is placed on a matrix with a simple stiffness gradient, directional migration called durotaxis emerges because of the asymmetric extension and contraction of the pseudopodia, which is accompanied by the asymmetric distribution of focal adhesions. Similarly, to determine cell migration on a matrix with cell-scale stiffness heterogeneity, the interaction between cell-scale stiffness heterogeneity and cellular responses, such as the dynamics of the cell-matrix adhesion site, intracellular prestress, and cell shape, should play a key role. In this review, we summarize systematic studies on the dynamics of cell migration, shaping, and traction force on a matrix with cell-scale stiffness heterogeneity using micro-elastically patterned hydrogels. We also outline the cell migration model based on cell-shaping dynamics that explains the general durotaxis induced by cell-scale stiffness heterogeneity. This review article is an extended version of the Japanese article, Dynamics of Cell Shaping and Migration on the Matrix with Cell-scale Stiffness-heterogeneity, published in SEIBUTSU BUTSURI Vol. 61, p. 152–156 (2021).